Contribution of foods to absolute nutrient intake and between-person variations of nutrient intake in Korean preschoolers - Kang, Minji (Nutr Res Pract, 2019)
BACKGROUND/OBJECTIVES: The aim of this study was to analyze specific foods influencing absolute nutrient intake and between-person variations of nutrient intake among Korean preschoolers. SUBJECTS/METHODS: This study included 2,766 participants aged 1–5 years in the 2009–2013 Korea National Health and Nutrition Examination Surveys. Dietary data were obtained from a 24-h dietary recall method. Major food sources of absolute nutrient intake were evaluated based on percent contribution of each food. To assess the contribution of specific foods to between-person variations in nutrient intake, stepwise multiple regressions were performed and cumulative R(2) was used. RESULTS: White rice and milk were main food sources of energy, protein, carbohydrate, phosphorus, iron, potassium, thiamin, riboflavin, and niacin. The percentage of fat contributed by milk was 21.3% which was the highest, followed by pork, soybean oil, and egg. White rice accounted for 25% and 40% of total variability in total energy and carbohydrate intakes, respectively. About 39% of variation in calcium intake was explained by milk while 40% of variation in phosphorous intake was explained by cheese. The top 10 foods contributing to between-person variations in nutrient intakes were similar with food items that mainly contributed to absolute nutrient intakes. The number of foods explaining 90% of absolute amounts of nutrient intakes varied from 28 for vitamin A to 80 for iron. CONCLUSIONS: This study identified specific foods that contributed to absolute nutrient intakes and between-person variations in nutrient intakes among Korean preschoolers. Our findings can be used to develop dietary assessment tools and establish food-based dietary guidelines for young children.